Pharmaceutical involvement in Infectious Disease control: Strategies, Challenge and Solutions - Norma Winata; Dadang Muhammad Hasyim; Brevmana Anugrah Primulyanto (Pt. Anagata Sembagi Education, 2024)
This study aims to explore the role of the pharmaceutical sector in controlling infectious diseases, focusing on strategies, challenges, and solutions that can be implemented. The research method used is Systematic Literature Review (SLR) to collect and analyze data from related literature. Inclusion criteria include articles published in the last ten years, using English or Indonesian, and discussing pharmaceutical strategies in controlling infectious diseases. The literature search process was carried out through scientific databases such as PubMed, Scopus, and Google Scholar. The results of this study are Infectious disease control strategies involve the development of new vaccines and drugs, efficient drug distribution, and public education. The pharmaceutical sector plays an important role in creating medical solutions and implementing vaccination campaigns. The main challenge is antimicrobial resistance, which is caused by the unwise use of antibiotics. To overcome this challenge, public education, strict supervision in health facilities, and the development of new drugs are needed. The application of digital technology, such as AI-based applications, can also help monitor drug use and provide early warnings about the spread of disease. The role of pharmacists is vital in providing information and education about disease prevention, correct drug use, and the importance of vaccination. With innovative solutions such as the development of emergency pharmaceutical packages, the implementation of e-prescription, and technology-based training for pharmacists, it is hoped that the global health system can be more resilient in dealing with infectious disease outbreaks. Collaboration between the pharmaceutical sector, governments, and international organizations is essential in strengthening infectious disease control efforts and improving the readiness of the global health system.